Concentrations of toxic metals in water, soil and sediment of rio Formoso, TO (Research, Society and Development, 2021)
On the banks of the Rio Formoso, Tocantins, Brazil, they are surrounded by numerous irrigation projects for agricultural purposes, which use water resources. The objective of this investigation was the determination of barium, chromium, copper, zinc, nickel, lead, iron and aluminum by means of a Microwave Plasma Atomic Emission Spectrometer (MP-AES) in water, soil and sediment, and physical characterization -Chemical purpose of this investigation was determination of metals barium, chromium, copper, zinc, nickel, lead, iron and aluminum only. How they were collected in four campaigns (between April 2018 and February 2019). The concentration of most metals in water, if known within the legal values (CONAMA 354/05). In addition to aluminum and iron, which have a naturally high concentration in Tocantins waters, concentrated barium is high compared to other metals. In soil regions, the values of Cr and Ba are above those allowed by CONAMA 460/13. In the sediment, the Cr also centered high (CONAMA 344/05). Although the concentration of metals is not present outside legal standards, they are above the VRQ (quality reference values) for most states. The distribution of metals in environmental compartments after Principal Component Analysis (PCA), distinct performance, Al and Fe distributed in water, Mn in sediment and Cr and Ba in soil. Metal rates are higher in points sampled with greater proximity to agricultural activities, which causes concern, with the advance of agriculture in the region, and the increase in agricultural inputs for this production.